Pengaruh Daya Tarik Iklan Melalui Instagram Dan Minat Beli Terhadap Keputusan Pembelian Pada Luar Garis Coffee - Hermawan, Fadly Dwi; Saputra, Asron (LPPM Universitas Putera Batam, 2024)
This research or observation have main goal to known the influece of interest buyingand interest advertising that to purchase decision on Luar Garis Coffee. The location forthe object reserch is in Batam, it is Luar Garis Coffee. The population in this observation isthe consumer that buying a product`s in Luar Garis Coffee. This research have 7.776people as the population and the sample is 380 people. The research isi usingnonprobability sampling for the technique sampling. the The data in this researc will collectby the questionnaire and going to process by SPSS V.26 aplication from IBM Statistic. Allthe sample in this observation will fill the questionnaire. from the data that have beencollect, the result from analysis by the SPSS V.26 is the interest buying and interestadvertising can influence purchase decision on Luar Garis Coffee. We can see the FValue, it is 295,36.